2021
DOI: 10.1037/rev0000284
|View full text |Cite
|
Sign up to set email alerts
|

Equal evidence perceptual tasks suggest a key role for interactive competition in decision-making.

Abstract: The dynamics of decision-making have been widely studied over the past several decades through the lens of an overarching theory called sequential sampling theory (SST). Within SST, choices are represented as accumulators, each of which races toward a decision boundary by drawing stochastic samples of evidence through time. Although progress has been made in understanding how decisions are made within the SST framework, considerable debate centers on whether the accumulators exhibit dependency during the evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…Second, evidence accumulation models offer a variety of distinct mechanisms to account for competition between response alternatives, including rich-get-richer dynamics (or closely related lateral inhibition), and normalization of evidence (Teodorescu & Usher, 2013). Third, an increasing number of studies have highlighted the role of the absolute level of support (in addition to relative support) for selected and nonselected response alternatives in evidence accumulation (Kirkpatrick et al, 2021; Simen et al, 2016; Teodorescu et al, 2016; van Ravenzwaaij et al, 2020). Thus, evidence accumulation models are, in principle, well-equipped to explain the latent cognitive dynamics giving rise to empirically observed associations and the speed with which they are generated.…”
Section: Previous Process Models Of Free Associationmentioning
confidence: 99%
“…Second, evidence accumulation models offer a variety of distinct mechanisms to account for competition between response alternatives, including rich-get-richer dynamics (or closely related lateral inhibition), and normalization of evidence (Teodorescu & Usher, 2013). Third, an increasing number of studies have highlighted the role of the absolute level of support (in addition to relative support) for selected and nonselected response alternatives in evidence accumulation (Kirkpatrick et al, 2021; Simen et al, 2016; Teodorescu et al, 2016; van Ravenzwaaij et al, 2020). Thus, evidence accumulation models are, in principle, well-equipped to explain the latent cognitive dynamics giving rise to empirically observed associations and the speed with which they are generated.…”
Section: Previous Process Models Of Free Associationmentioning
confidence: 99%
“…when, compared with a baseline condition, the magnitude of the alternatives is increased by keeping either difference or ratio between alternatives constant [11]; similarly, in other studies that compared models extensively, race models performed poorly when fitted to data [58]. For these reasons [2,11,58], this account is not generally considered as a plausible candidate in investigations about magnitude-sensitivity.…”
Section: Race Modelsmentioning
confidence: 99%
“…Other accumulator model architectures, like the simple accumulator or recruitment model (Audley & Pike, 1965;La Berge, 1962), the Poisson counter model (Smith & Van Zandt, 2000;Townsend & Ashby, 1983), and the Vickers accumulator (Smith & Vickers, 1988;Vickers, 1970Vickers, , 1979, give poorer RT distribution predictions than models based on racing diffusion processes . Usher and McClelland (2001) proposed a model with mutual inhibition between the accumulators on grounds of neural plausibility and some researchers have reported that these kinds of models give a better fit to data (Ditterich, 2006;Kirkpatrick et al 2021). Others have found that models with independent accumulators give good accounts of data Smith & Ratcliff, 2009;Tillman et al 2020) including neural data.…”
Section: Neurally-principled Models Of Decision Makingmentioning
confidence: 99%
“…Lateral inhibition in race-model architectures has recently been implicated in the absoluteintensity or absolute-value effect (Kirkpatrick et al, 2021;Ratcliff et al, 2018;Teodorerscu & Usher, 2013;Teodorescu et al, 2016). This is the finding that decisions about differ- still perform better than any of reduced versions of it for a majority of participants.…”
Section: Drift Rate Variabilitymentioning
confidence: 99%